Glycan masking of a non-neutralising epitope enhances neutralising antibodies targeting the RBD of SARS-CoV-2 and its variants - Carnell, George W.; Billmeier, Martina; Vishwanath, Sneha; Suau Sans, Maria; Wein, Hannah; George, Charlotte L.; Neckermann, Patrick; Del Rosario, Joanne Marie M.; Sampson, Alexander T.; Einhauser, Sebastian; Aguinam, Ernest T.; Ferrari, Matteo; et al. (Frontiers in Immunology, 2023)
The accelerated development of the first generation COVID-19 vaccines has saved millions of lives, and potentially more from the long-term sequelae of SARS-CoV-2 infection. The most successful vaccine candidates have used the full-length SARS-CoV-2 spike protein as an immunogen. As expected of RNA viruses, new variants have evolved and quickly replaced the original wild-type SARS-CoV-2, leading to escape from natural infection or vaccine induced immunity provided by the original SARS-CoV-2 spike sequence. Next generation vaccines that confer specific and targeted immunity to broadly neutralising epitopes on the SARS-CoV-2 spike protein against different variants of concern (VOC) offer an advance on current booster shots of previously used vaccines. Here, we present a targeted approach to elicit antibodies that neutralise both the ancestral SARS-CoV-2, and the VOCs, by introducing a specific glycosylation site on a non-neutralising epitope of the RBD. The addition of a specific glycosylation site in the RBD based vaccine candidate focused the immune response towards other broadly neutralising epitopes on the RBD. We further observed enhanced cross-neutralisation and cross-binding using a DNA-MVA CR19 prime-boost regime, thus demonstrating the superiority of the glycan engineered RBD vaccine candidate across two platforms and a promising candidate as a broad variant booster vaccine.